In Search of a New Social Contract: Polarization over the Aims of Higher Education in Türkiye and the Promise of Comparative Political Theory - Taşgetiren, Ömer; Taşgetiren, Ömer (Brill Academic Publishers, 2026)
To address the negative effects of political polarization on social cohesion, trust, and democratic deliberation, this article tackles the dispute between conservative and non-conservative groups in Türkiye over the aims of higher education and examines the possibility of reaching common ground between these polarized groups to create a new social contract. The article contends that comparative political theory, when viewed as a component of liberal education, offers ideas that can serve as a constructive framework for restructuring university curricula and academics’ teaching practices. Such a liberal vision of comparative political theory can incorporate non-Western political ideas into university curricula without sacrificing liberal concerns about the cultivation of individual autonomy. While this approach may not appeal to those who seek to shape education according to their worldview, it offers a shared framework for those genuinely concerned about the harmful effects of polarization.
Keywords: Comparative Social Sciences; Social Sciences; Social & Political Philosophy; Philosophy